Avaliação da virulência e susceptibilidade a antimicrobianos em Streptococcus agalactiae isolados de mastite bovina de rebanhos brasileiros - Silva, Juliana Rosa da (2015)
Streptococcus agalactiae is one of the major causal agents of mastitis in cattle, which causes economic losses to cattle breeders. However, there are few studies related with evaluation of virulence and susceptibility of these antimicrobial agents toward cattle samples in Brazil, so far. In this work, we aimed to assess the frequency of virulence genes, namely, hylB, bca, bac, fbsA, fbsB, cfb, bibA, PI-1, PI-2a and PI-2b; antimicrobial agent resistance genes, namely, ermA, ermB, mefA, tetO, tetM, aphA3 and aad-6; susceptibility to antimicrobial agents such as erythromycin, clindamycin, tetracycline, gentamicin, penicillin, ceftiofur, cephalothin, sulfonamide; as well as the association between genotype and resistance phenotypes in 61 isolates of S. agalactiae obtained from mastitis cases in herds of Brazilian cattle. Seven virulence profiles related to gene frequencies were set. The genes cfb, hylB, fbsB and PI-2 (PI-2a or PI-2b) were found in all isolates; while PI-1 was only found in one isolate, fbsA was found in 27 isolates (44%), bibA in 9 isolates (15%), bca in two isolates (3%), and bac was found in none of the isolates. Regarding the resistance genes, ermB was found in 12 isolates (19.67%), tetO in 20 isolates (32.78%), and tetM was found in 9 isolates (14.75%). The following genes were not detected: ermA, mefA, apha3 and aad6. There was association between the presence of genes ermB, tetM and tetO, and resistance phenotypes to erythromycin, clindamycin and tetracycline. Different resistance indices were found by means of minimum inhibitory concentration test, namely for erythromycin (26.23%), tetracycline (47.54%), gentamicin (3.28%), sulfonamide (98.36%), and clindamycin (29.51%). In other hand, all isolates were susceptible to penicillin, ceftiofur and cephalothin. Then, we could state that these isolates have diverse determining factors for virulence, however, with a common core represented by genes cfb, hylB, fbsB and PI-2 (mainly PI-2b). In addition, the antimicrobial resistance tests can help in making decisions related to these treatments, because the resistance to various antimicrobial agents was found to show high relative frequency for this pathogen.